Layered Black Phosphorus as a Selective Vapor Sensor - Mayorga-Martinez, Carmen C. (2016)
Black phosphorus is a layered material that is sensitive to the surrounding atmosphere. This is generally considered as a disadvantage, especially when compared to more stable layered compounds, such as graphite or MoS2. This sensitivity is now turned into an advantage. A vapor sensor that is based on layered black phosphorus and uses electrochemical impedance spectroscopy as the detection method is presented; the device selectively detects methanol vapor. The impedance phase measured at a constant frequency is used as a distinctive parameter for the selective quantification of methanol, and increases with the methanol concentration. The low detection limit of 28 ppm is well below the approved exposure limit of 200 ppm. The results are highly reproducible, and the vapor sensor is shown to be very selective in the presence of other vapors and to have long-term stability.